DIFFERENCES IN CLINICAL AND LABORATORY CHARACTERISTICS IN PATIENTS INFECTED WITH COVID-19 DURING DIFFERENT WAVES OF THE PANDEMIC - Barać, Aleksandra; Despotović, Aleksa; Vujović, Ankica; Cucanić, Teodora; Cucanić, Ksenija; Mitić, Ana; Stjepanović, Mihailo; Marić, Nikola; Filipović, Ana; Vlašković, Jelena; Knežević, Nataša; Stojanović, Maja; et al. (Medical Research, 2023)
Introduction/The Aim: So far, throughout the COVID-19 pandemic, major epidemic waves have been observed affected more than 656 million people. Epidemiological studies have confirmed variability of clinical presentation of SARS-CoV-2 infection throughout these epidemic waves. During this period, virus mutations have contributed to a greater challenges when it comes to treatment and prevention. The aim of the study is to determine the differences in clinical presentation, laboratory parameters, as well as the treatment outcome of patients suffering from COVID- 19 during four different waves of pandemic caused by different genotypic and phenotypic variants of SARS-CoV-2. Material and Methods: A retrospective study was conducted during which data were collected and analysed from hospitalised patients at the University Clinical Center of Serbia Clinic for Infectious and Tropical Diseases in period during March 1, 2020 to December 1, 2021. Statistical analyses, socio-epidemiological, clinical, radiographic and laboratory characteristics of patients through different waves of the COVID-19 pandemic were compared. Results: Study included 523 patients. Elevated body temperature was the first and most common symptom of COVID-19 infection during all 4 waves of pandemic, although cough and malaise were most common symptoms in fourth wave. Cough symptom after elevated temperature in third wave (p<0.05), and malaise in second wave. Diarrhoea and nausea were statistically significantly more frequent in the fourth wave compared to the previous waves (p=0.04 and p=0.02). Conclusion: Highest values of inflammatory biomarkers were found in second and fourth wave. Fourth wave was characterized by largest number of hospitalized patients and it represented the peak of the pandemic. Treatment options varied throughout the waves, as corticosteroids use was most commonly during the fourth epidemic wave in hospital.